(untitled) (Global Journal of Medical Research, 2020)
In 2019 a new virus named severe acute respiratory syndrome coronavirus 2 emerged in Wuhan City of Hubei Province of China causing and exerted a massive toll over the world By World Health Organization it was subsequently named COVID 19 Corona virus disease It is considered as a relative of severe acute respiratory syndrome SARS and Middle East respiratory syndrome MERS Within months after its emergence in China it had affected more than seven lakhs lives and caused more than thirty thousand deaths The general clinical symptoms associated with COVID 19 patients include fever dry cough generalized body pain and shortness of breath Its high transmission potential highlighted the need for a coordinated global response to contain such disease threats Treatment is essentially symptomatic and primary intervention being used is social distancing Hence special attention and efforts should be implemented to control the current outbreaks The present review was constructed to elaborate the Corona virus disease and to investigate the most recent trend in India